(3GdJbQjH hGdJjSjQ deYQaI Sff GdHTjQ GdfPjQs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s
(3ChdgG (B:s
(3aEf Yde GdMOjK ef GaVd GdbQH Edi QH GdYGdejf hcja dG jchf hgh HjGf WQjb NjQ GdNdb s
(3BNQgG (B:s
(3hbO QhjJ ai GdEQTGO gfG KdGKI CMGOjK HCSGfjO cdge OeTbjhf efi Bd QShd Gddg hGfG OeTbi s
(3eNJUQ debOeI Hf GdUdGM ai GdeUWdMs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs